The position of woman and their role from the perspective of Al Tariqah Al-Aliyah Qadiriyya Al-Kasnazaniyya - Qais H. A. Abuyounis; Muhamad Faisal Ashaari; Mohamad Zulkifli Abdul Ghani; Abu Dardaa Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sufism has distinguished itself throughout Islamic history by offering many solutions and gifts for various social issues and problems, due to the spiritual awareness and comprehensive application of the principles of Islam. This study aims to shed light on the philosophy and perspective of the Qadiriyya Al Kasnazaniyya Sufi order regarding women and their status, especially in light of the Western and feminist calls in Arab and Islamic societies to break free from societal and religious constraints. The researcher utilized a descriptive-analytical approach to track the books and activities of the Al-Kasnazaniyya order to clarify their vision and methodology in dealing with the topic of women. Additionally, the researcher relied on field research and personal interviews with the leader of the Al-Kasnazaniyya order and its followers to ensure obtaining information directly from the source and understanding the Al-Kasnazaniyya vision and reaching the desired results. The study has reached several important results, the most important of which are: in the Sufi concept of Al-Khasnazani, women have a place and interest three times greater than men, as the head of the Al-Khasanzani method explains, due to the roles entrusted to them of guidance, upbringing, reform, preparation, support for men, and raising awareness among the younger generation and guiding them towards the enlightened methodology of Prophet Muhammad. Secondly, the Al-Khasanzani disciple, whether male or female, is distinguished by having many duties and must possess a set of qualities that qualify them to be a soldier and guardian of the Prophet's law, and to be diligent in lifting injustice and corruption from the community, and to be a compass for guiding others and reforming society. Thirdly, the method takes great care of women so that they do not become commodities or fall into the hands of the devil and his soldiers who try to deceive them, and to bring them out of their sound nature. The method's interests vary on several aspects, starting from the religious, educational, and guidance aspects to the societal aspect, ultimately achieving their needs and obtaining their political and societal rights, and assuming their leadership role in preparing generations according to the methodology of the Prophet Muhammad and his noble and his pure family.